Ethical Frameworks for AI Deployment in Financial Decision-Making: Balancing Profitability and Social Responsibility - Jeffrey Chidera Ogeawuchi; Aadit Sharma; Bolaji Iyanu Adekunle; Abraham Ayodeji Abayomi; Omoniyi Onifade (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2024)
The integration of artificial intelligence into financial decision-making has introduced transformative efficiencies and competitive advantages across domains such as algorithmic trading, credit risk assessment, fraud detection, and customer profiling. However, these advancements raise profound ethical concerns, particularly in high-stakes environments where opaque models and biased algorithms can perpetuate discrimination, reduce accountability, and compromise consumer trust. This paper critically investigates the ethical implications of AI-driven financial systems, emphasizing the risks of algorithmic bias, the challenge of model interpretability, and the urgency of safeguarding data privacy. By drawing on normative ethical principles—fairness, accountability, transparency, and human oversight—the study proposes a comprehensive governance framework to guide the ethical lifecycle of AI deployment in finance. It evaluates the role of financial institutions, regulatory bodies, and central banks in setting enforceable standards, while offering a practical model for integrating ethics from design to audit. The paper concludes by reflecting on the responsibilities of key stakeholders and outlining future research and policy directions to ensure that AI innovations support not only profitability but also inclusive and socially responsible financial ecosystems.